Ejaculate Fractioning Effect on Llama Sperm Head Morphometry as Assessed by the ISAS® CASA system. Issue 1 (6th September 2013) - Soler, C; Sancho, M; García, A; Fuentes, MC; Núñez, J; Cucho, H
Contents: South American camelid sperm characteristics are poorly known compared with those of other domestic animals. The long‐term duration of ejaculation makes difficult to gather all the seminal fluid, implying possible ejaculation portion losses. Thus, the aim of this research was to evaluate the characteristics of the morphology and morphometry of the spermatozoa change during ejaculation. The morphometric characterization was tested on nine specimens of the Lanuda breed, using a special artificial vagina. In five of the animals, a fractioning of the ejaculate was performed by taking samples every 5 min. for a total of 20 min. Air‐dried seminal smears were stained with Hemacolor and mounted permanently with Eukitt. Morphometric analysis was carried out with the morphometry module of the ISAS ® CASA system. Almost 350 cells were analysed per sample, with a total number of 3207 spermatozoa. Mean values were given as follows: length: 5.51 μm; width: 3.38 μm; area: 17.75 μm 2 ; perimeter: 14.8 μm; ellipticity: 0.24; elongation: 0.56; rugosity: 0.87; regularity: 1.07; and shape factor: 1.41. Different animals showed differences in their morphometric values. When we compared the values from different fractions, only two samples showed differences in morphometric parameter values and four samples showed differences in shape parameters. Multivariate analysis allowed the size classification of the cells into three classes and five classes of shapes. The distribution of classes among fractions showed no differences. Despite the individual morphometric differences observed in some fractions, the characteristics of the sperm head morphometry can be considered constant along the ejaculatory period in the llama.